A systematic approach to emergent breast free flap takeback: Clinical outcomes, algorithm, and review of the literature. Issue 7 (14th August 2013) - Khansa, Ibrahim; Chao, Albert H.; Taghizadeh, Maakan; Nagel, Theodore; Wang, Duane; Tiwari, Pankaj
<x xml:space="preserve">Abstract</x> Background Few evidence‐based and detailed algorithms exist on the management of failing breast free flaps, including use of the numerous salvage tools that are available. The purpose of this study was to analyze our outcomes with an algorithmic approach to breast free flap salvage after vascular compromise. A review of the literature is also presented. Methods A retrospective review of all breast free flaps performed at our institution between 2007 and 2012 was performed. Flaps with intraoperative and postoperative vascular complications were analyzed. Results A total of 612 microsurgical breast reconstructions in 442 patients were reviewed. Of these, 72 (11.8%) flaps had intraoperative vascular complications, and 36 (5.9%) had postoperative vascular complications. The total flap loss rate was 2.8%. The most commonly used salvage modalities were anastomotic revision (72%), heparin irrigation (72%), systemic heparin (37%), Fogarty catheter thrombectomy (17.6%), thrombolytics (13%), and indocyanine green angiography (10.2%). In 53 (49.1%) cases, flap salvage involved use of 1 modality, whereas in 55 (50.9%) cases multiple modalities were used. Factors associated with failure of these flap salvage tools included intraoperative arterial rather than postoperative arterial compromise (P = 0.01), and situations requiring use of a greater number of salvage modalities (P < 0.001). Conclusions We found that intraoperative compromise had significantly better prognosis than postoperative compromise. By organizing the numerous salvage modalities available to microsurgeons into a well‐defined algorithm that is supported by the literature, we have established a best practices protocol that has achieved flap salvage rates that compare favorably to the published literature. © 2013 Wiley Periodicals, Inc. Microsurgery 33:505–513, 2013.